Generating the artistic shapes using superformula / Rafizah Kechil, Zuraira Libasin and Wan Anisha Wan Mohammad - Kechil, Rafizah; Libasin, Zuraira; Wan Mohammad, Wan Anisha (Universiti Teknologi MARA, Pulau Pinang, 2015)
Geometric modelling has been used in designing various artistic shapes since year 1940. Most of the Computer Aided Design (CAD) and Computer Aided Geometric Design (CAGD) used spline, B-spline, Beta-spline, Hermite and Bezier in the designing process. This paper presents an alternative way to generate the artistic shapes with free form surface by using superformula namely Gielis formula in bipolar cylindrical coordinate. In Gielis formula, there are six parameters that can be changed to get different design. Random values for the parameters have been chosen. Mathematical software namely Maple has been used to design the artistic shapes. The equation and method that will be discussed in this paper can be used as a guideline in designing new potential design in manufacturing industry.